Voyages et utopie scientifique dans La Nouvelle Atlantide de Bacon - Mickaël Popelard (Etudes Epistémè)
Because it is a fiction drawing upon the Utopian genre, the New Atlantis is one of Bacon’s most original works. In this paper I explore the links between this voyage narrative and Bacon’s philosophy of science and suggest that the New Atlantis may be read as a fictional illustration of Bacon’s epistemology. For Bacon, travel is both a metaphor and a powerful instrument of science. Indeed knowledge should be based on as comprehensive a natural history as may be gathered, and travelling allows one to discover new natural facts. Yet the New Atlantis contrasts two groups of travellers who embody two conflicting attitudes towards nature. Whereas the European sailors never seek to go beyond appearances, the Bensalemite explorers are determined to put nature to the test and « torture » her. Bacon therefore distinguishes between a passive relationship to nature and an active one that may be seen as truly scientific. By pitting the Europeans against the Bensalemites and by imagining a remote ideal society where scientists have all but taken the place of the monarch, Bacon produces a literary text that goes further than most of his philosophical works.